Respuesta :
Let, the original price of the sneakers be $x.
Given, Mr. Richard paid $3 less that half of the original price.
Half of the original price = $[tex] \frac{x}{2} [/tex]
So Mr. Richard paid = $[tex] (\frac{x}{2}-3) [/tex]
By buying the sneakers Mr. Richard saved = $37.
That means the subtraction of the original price and the amount Mr. Richard paid is $37.
So we can write the equation as,
[tex] x-(\frac{x}{2}-3) = 37 [/tex]
[tex] x-\frac{x}{2}+3 = 37 [/tex]
To solve it for x, first we have to move 3 to the right side by subtracting it from both sides, we will get,
[tex] x-\frac{x}{2}+3-3 = 37-3 [/tex]
[tex] x-\frac{x}{2}= 37-3 [/tex]
[tex] x-\frac{x}{2} = 34 [/tex]
We will subtract the left side now. To subtract fractions we will make the denominators same. Here 2 is the denominator. To make the denominator of x as 2, we will multiply the numerator and denominator of x by 2. So we can write x as [tex] \frac{2x}{2} [/tex].
[tex] \frac{2x}{2} - \frac{x}{2} = 34 [/tex]
[tex] \frac{(2x-x)}{2} = 34 [/tex]
[tex] \frac{x}{2}= 34 [/tex]
Now we will multiply both sides by 2 to get x.
[tex] (\frac{x}{2})(2) = (34)(2) [/tex]
[tex] x = (34)(2) [/tex]
[tex] x = 68 [/tex]
So, the original price = $68.
Mr. Richard paid = $([tex] (\frac{68}{2} -3) [/tex] =$ [tex] (34-3) [/tex]= $[tex] 31 [/tex]
So we have got the required answer.
Mr. Richard paid $31 for the sneakers.